REDUCING CIGARETTE EXCISE TAXES WILL BENEFIT THE ECONOMY OF NEW YORK STATE (Tufts Archival Research Center, 2007)
Document containing arguments for reducing the state cigarette tax in New York. Claims that a reduction in the tax rate will be an economic stimulus for the state since it would allow convenience stores and other small businesse to employ more people.